2021
DOI: 10.3390/en14061518
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Cavitation Flow and Its Effect on the Structural Integrity of Multi-Stage Orifice

Abstract: Flow leakage due to cavitation erosion occurred at the socket welding part downstream of the multi-stage orifice installed in the auxiliary feedwater (AFW) pump recirculation line of the domestic nuclear power plant (NPP). To assess the adequacy of the changed operating flow rate proposed by a domestic NPP operator as the corrective measure concerning the flow leakage in the AFW pump recirculation line, the pattern of the cavitation flow in the eight-stage orifice and the connecting pipe depending on the magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this case, two operating conditions of the inlet velocity and the wall roughness at the venturi tube boundary are considered uncertain parameters, and the QoI are the cavitation area and the profiles of void fraction and velocity. In this regard, one of the present co-author [15,16] successfully predicted the location of flow leakage caused by the cavitation erosion and found that the averaged vapor volume fraction tended to increase as the surface roughness decreased in the multistage orifice.…”
Section: Introductionmentioning
confidence: 92%
“…In this case, two operating conditions of the inlet velocity and the wall roughness at the venturi tube boundary are considered uncertain parameters, and the QoI are the cavitation area and the profiles of void fraction and velocity. In this regard, one of the present co-author [15,16] successfully predicted the location of flow leakage caused by the cavitation erosion and found that the averaged vapor volume fraction tended to increase as the surface roughness decreased in the multistage orifice.…”
Section: Introductionmentioning
confidence: 92%
“…The default maximum number of modes for the solver is 6. These modes are the rigid body modes that each object has, that is, the translational modes in 3 directions and the rotational modes in 3 directions, so the maximum number of modes needs to be increased (only the first 6 modes are considered for tubing modal analysis) [27] to find the corresponding modal at more frequencies. Here, the maximum number of modes is increased to 20.…”
Section: Simulationmentioning
confidence: 99%